O ensino da leitura do gênero fábula: um recurso funcional no ensino da Língua Portuguesa - Araújo, Betânia Ferreira de (2017)
Currently, there is a consensus that, in the learning process of reading and writing, the activity carried out by the teacher must be supported by social practices. For this, the teacher should have the diversity of textual genres present in society. Freire (1987) argued that the contents of socially circulating texts are not disconnected fragments of totality, but a world of knowledge expressed, often through popular knowledge, in defending the contextualization of the teaching of the mother tongue (reading and writing). Much of the linguistic research shows that the child, who has contact with literature at an early age, benefits in many ways, such as accumulating ideas and getting close to the contact with the structure of writing by listening to the text itself. This work aims to present a research on the process of reading through the fables genre, in the 4th year of elementary school, to know the difficulties and to increase the critical capacity of the students. This genre was chosen because it is a brief narrative, adequate for this age group and demands a critical reflection. Theoretically, we rely on Marcuschi (2008), Dolz and Schneuwly (2004), between others. The method used was the action research (SEVERINO, 2007), which in addition to understanding the investigative process, intends to intervene and modify the researched situation Methodologically, we carried out evaluations on the reading capacity of 11 students from a public school in the Municipality of Olinda - PE and we developed didactic sequences to increase critical capacity. We seek to obtain as answer the contribution of the fable genre in the development of reading and in the construction of the meaning of the text, seeking to work the critical census of the teachers focusing on the implicit of the genre in question.